PHYSICAL ACTIVITY AND POSTURAL STABILITY AMONG INDONESIAN CONSTRUCTION WORKERS: A PRELIMINARY STUDY - Marufa, Siti Ainun; Rahmawati, Nurul Aini; Ramdini , Ega Halima; Putri, Firza Nadia (The Indonesian Journal of Public Health, 2024)
Introduction: The higher workloads experienced by construction workers reflect the higher physical demands of construction work. Prolonged workloads are responsible for up to 60% of chronic fatigue, diseases, and injuries among construction workers. Individuals need to develop their balance to support physical activity in order to improve their quality of life. Abnormalities in the balance of construction workers is associated with an increased risk of falls. Aims: This preliminary study aims to assess the relationship between physical activity and postural stability among Indonesian construction workers. Methods: A total of 118 healthy male construction workers without health problems were recruited for this study. Their physical activity levels were measured using the Baecke questionnaire for work, sports, and leisure time, while their postural balance was assessed using the one-leg standing test. Results: This study found a significant difference between physical activity in sports and during leisure time compared to activity at work (F 2.234 = 149.3, p < 0.0001). In addition, this study found a weak correlation between physical activity at work and postural stability among construction workers (p = 0.006, r = -2,498). Conclusion: These preliminary findings indicated that construction workers had higher levels of physical activity at work. However, no correlation was found with postural stability. Further research is needed to investigate larger sample sizes with similar characteristics.